The Contribution of The Qur'an Educational Park to Character Development - Karenina Panca Kiranti; Ersis Warmansyah Abbas; Mutiani Mutiani (Journal of Social Development, 2023)
Character development can be organized in formal schools and non-formal schools such as the Al-Qur'an Education Park; this is evident from the activities at the Al-Qur'an Education Park that can be implemented in character development. This service aims to optimize students' character development from the Ar-Raudhah Banjarmasin Al-Qur'an Education Park. The method used in this service is direct assistance, such as Murajaah activities, reading the Qur'an, and lecture activities about the stories of the Prophet. The results of this service activity are three activities that can help character development. The three activities are murajaah activities, Qur'an reading activities and lecture activities on the stories of the Prophet.